Peran Citra Merek dan Layanan Customer Terhadap Loyalitas Nasabah Bank - Izzaini, Muhammad Fadhil (Maliki Interdisciplinary Journal, 2024)
This research discusses the influence of brand image and customer service on customer loyalty in the context of an increasingly competitive banking industry. Brand image, which reflects consumers’ perceptions and beliefs about the company, is important and interesting in the discussion of retaining customers. Research shows that the brand image presented by the company affects customer trust, which will then continue at the level of increasing loyalty. In addition, the quality of customer service is also a key factor in creating a positive experience for customers. Service that is responsive, empathetic, satisfying and available 24/7 can increase customer satisfaction, which then becomes a mediator between brand image and loyalty.